Illumination of cell cycle progression by multi-fluorescent sensing system. Issue 12 (18th June 2019) - Liu, Shuo; Li, Jun; Wang, Teng; Xu, Jiawen; Liu, Zhipei; Wang, Haobin; Wei, Gong-Hong; Ianni, Alessandro; Braun, Thomas; Yue, Shijing
ABSTRACT: Multi-fluorescent imaging of cell cycle progression is essential for the study of cell proliferation in vitro and in vivo . However, there remain challenges, particularly to image cell cycle progression in living cell with available imaging techniques due to lacking the suitable probe. Here, we design a triple fluorescent sensors system making the cell cycle progression visible. Multi-fluorescent sensor shows the proliferating or proliferated cells with different colors. We thus generate the construct and adenovirus to probe cell cycle progression in living cell lines and primary cardiomyocytes. Furthermore, we create the knock-in transgenic mouse to monitor cell cycle progression in vivo . Together, the system can be applied to investigate cell proliferation or cell cycle progression in living cells and animals.